2012
DOI: 10.1371/journal.pone.0030632
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Co-Localisation Measurement Utilising Z-Stack Image Intensity Similarities for Biological Studies

Abstract: BackgroundCo-localisation is a widely used measurement in immunohistochemical analysis to determine if fluorescently labelled biological entities, such as cells, proteins or molecules share a same location. However the measurement of co-localisation is challenging due to the complex nature of such fluorescent images, especially when multiple focal planes are captured. The current state-of-art co-localisation measurements of 3-dimensional (3D) image stacks are biased by noise and cross-overs from non-consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…Thus, we confirmed that pixel randomization leads to false positive colocalization compared to spot randomization . Finally, we underline that spot randomization is based on synthetic images, and requires to define and estimate image model parameters (noise, intensity, number of spots; ).…”
Section: Pixel‐based Methodssupporting
confidence: 69%
“…Thus, we confirmed that pixel randomization leads to false positive colocalization compared to spot randomization . Finally, we underline that spot randomization is based on synthetic images, and requires to define and estimate image model parameters (noise, intensity, number of spots; ).…”
Section: Pixel‐based Methodssupporting
confidence: 69%
“…Afterwards, the cells were washed with 200 μL PBS once and 300 μL of fresh pre-warmed RPMI medium without phenol red was added prior to imaging by confocal microscopy using z-stack analysis (Supplementary Figs. 67 and 68 ) 80 . A laser diode emitting at 405 nm and a bandpass emission filter BP 420–480 nm were used for the excitation and emission collection of CNDs.…”
Section: Methodsmentioning
confidence: 97%
“…Both scenarios however can be distinguished using confocal microscopy. To confirm that the majority of fluorescence signal from CNDs associated with cells originates from internalized CNDs z-stacks were recorded 80 with CLSM (LSM 510, Zeiss, Germany) with a Pla N- Apochromat ×63/1.40 Oil DIC M27 objective. Herein, Calcein - AM (Molecular Probes) was applied to label living cells (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Of each cell with clear intracellular S. pneumoniae, individual pictures, and Z-stack series (green, red, and grey phase contrast) were taken with a Leica DM IRE2 inverted confocal microscope setup, and subsequently analyzed with ImageJ and its co-localization plug-in function (http://rsb.info.nih.gov/ij/). For the representative image a XY plane merger was created as well as 2 orthogonal views of the YZ and XZ plane [13] were also generated with ImageJ for illustrative purposes.…”
Section: Methodsmentioning
confidence: 99%